The growth-at-risk (GaR) Framework: Implication for Ukraine - Anastasiya Ivanova; Alona Shmygel; Ihor Lubchuk (Graduate Institute of International and Development Studies, 2021)
Using data for the Ukrainian economy, we applied and adapted the growth-at-risk (GaR) framework to examine the association between financial conditions, credit and sectors' activity, and external conditions and the probability distribution of GDP growth in Ukraine. We applied CSA and PCA approaches to construct indices of these partitions. We further derived GDP growth distributions and explored their behavior under different scenarios. Results from the model with PCA indices suggest that the relationships between financial conditions as well as external conditions indices and economic activity are inverse regardless of quantile of GDP distribution. Moreover, we found that the financial conditions index has the largest effect on the GDP growth on the lower quantiles, which could generate significant downside risk to the economy.
Keywords: C31; C53; E17; 330; quantile regression; economic growth; GDP; principal component analysis; GDP growth distribution